Destabilization of a laminar flow in a rectangular channel by transversely-oriented wall corrugation (Archives of Mechanics - Test, 2011)
Linear stability of the flow through the transversely corrugated channel with flat sidewalls is investigated numerically. Two variants of the wall corrugation are considered: symmetric sinusoidal waviness of the top and bottom walls and onesided corrugation, i.e., one of the walls remains flat. Spectrally accurate Galerkin method formulated in a transformed domain is used for the solution of the main flow and linear stability equations. Unstable normal modes have been identified and their parametric variation has been determined. The results show that for sufficiently large aspect ratios, the influence of the sidewalls is weak and the stability properties resemble those of the spanwise-periodic channel (investigated recently by the first author). It means that an appropriately designed transversal corrugation may be regarded as a promising method for passive enhancement of mixing in laminar regime.